PERBANDINGAN MORFOLOGI TUMBUHAN TERATAI (DAUN DAN BUNGA) PADA SPESIES Nymphaea pubecens Willd. dan Nymphaea nouchali Burm.f. Spesifik ASTAMBUL - Mariatul Qibtiyah; Muhammad Indar Pramudi; Jumar Jumar (Agroekotek View, 2021)
The lotuses that grow in the Astambul area include N. pubescens and N. naucali. There appears to be a difference in morphology in the leaves and flowers of the two types of lotus. The difference in leaf morphology was evident starting when N. pubescens had dark green leaves in the fields while N. naucali had light green or vanished green leaves. The canopy observation results showed the difference between N. pubescens and N. naucali, N. pubescens had a larger canopy compared to the slender N. naucali. More roots allow more nutrients to be absorbed by plants. The roots of N. pubescens have more roots than N. naucali so that the possibility of more nutrients being absorbed causes the formation of the crown is also greater. This research was conducted using a survey method on lotus plants in Astambul Village, Banjar Regency. Sampling was done by taking live plant species N. pubescens and N. nouchali. All collected specimens were examined in detail in the laboratory for different morphological characters of leaves and flowers. There are 5 samples of lotus plants taken at this land at 5 different locations in the two types of lotus so that the total sample size is 50 samples from each location. The lotus flower has 4 parts, namely the petals, the crown, the benangsari, and the pistil. N. pubescens flower has 4 petals dark green with pink tinge with slightly wider shape than N. naucali. N. naucali has 4 petals with a dark green tinge of light green color. N. pubescens has fewer crowns than N. naucali. The shape of N. pubescens is different from that of N. Naucali.